Pelaksanaan Pengukuran Ranah Kognitif, Afektif, Dan Psikomotor Pada Mata Pelajaran Ips Kelas Iii Sd Muhammadiyah Palangkaraya - Iin Nurbudiyani (Anterior Jurnal, 2013)
This procedure is also to eliminate subjectivity in research results. The sample in this study were all third grade students of Muhammadiyah Elementary School Palangkaraya, and because the population was less than 100 people, all third grade students of Muhammadiyah Elementary School became the research sample. The variables in this study are cognitive, affective and psychomotor domains. Data collection methods or techniques are using the question method or in the form of tests and observations. While the instrument used in this study is in the form of a test to measure the ability of the beginning or end of learning, and observation during the learning process takes place. The steps and procedures in analyzing data are as follows: data collection, editing, coding, data tabulation, data quality testing and describing data. In a learning process, it is always necessary to conduct an assessment or evaluation so that a teacher obtains complete data on the ability of students to have their abilities, assessment will also be meaningful when a teacher does not only do one or two assessments, but is done as often as possible to monitor student progress. continuously while looking at the extent to which learning objectives have been achieved. In addition evaluation must also be able to describe students' abilities in three domains, namely: cognitive, affective and psychomotor domains. To measure the cognitive domain using a measuring instrument in the form of multiple choice tests, while to measure the affective and psychomotor domains using the observation sheet.